2020
DOI: 10.3762/bjnano.11.79
|View full text |Cite
|
Sign up to set email alerts
|

Atomic layer deposition for efficient oxygen evolution reaction at Pt/Ir catalyst layers

Abstract: We provide a direct comparison of two distinct methods of Ti felt surface treatment and Pt/Ir electrocatalyst deposition for the positive electrode of regenerative fuel cells and vanadium–air redox flow batteries. Each method is well documented in the literature, and this paper provides a direct comparison under identical experimental conditions of electrochemical measurements and in identical units. In the first method, based on classical engineering, the bimetallic catalyst is deposited by dip-coating in a p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…[ 88 ] The same type of the composites was tested as the cathode material in fuel cells and vanadium‐air batteries. [ 89 ] Nanostructured Ir/TiO 2 electrodes prepared by a deposition of Ir‐films onto the surface of highly ordered TiO 2 nanotubes grown from Ti‐foils from ((EtCp)Ir(CHD)) and ozone at 220 °C exhibited excellent OER properties. The overpotential of OER in 0.1 m H 2 SO 4 was as low as 240 mV versus RHE at current density 10 mA cm −2 and mass activity 200 A g −1 at 340 mV with catalyst loading 160 µg cm −2 .…”
Section: Oermentioning
confidence: 99%
“…[ 88 ] The same type of the composites was tested as the cathode material in fuel cells and vanadium‐air batteries. [ 89 ] Nanostructured Ir/TiO 2 electrodes prepared by a deposition of Ir‐films onto the surface of highly ordered TiO 2 nanotubes grown from Ti‐foils from ((EtCp)Ir(CHD)) and ozone at 220 °C exhibited excellent OER properties. The overpotential of OER in 0.1 m H 2 SO 4 was as low as 240 mV versus RHE at current density 10 mA cm −2 and mass activity 200 A g −1 at 340 mV with catalyst loading 160 µg cm −2 .…”
Section: Oermentioning
confidence: 99%
“…This feature not only increases the concentration of active sites for catalytic reactions but also promotes efficient mass transport of reactants . In addition, the potential of ALD to tune the chemical composition and thickness of films enables the improvement of their performance and stability for OER. Accordingly, the method has gained significant attention in the development of electrocatalysts for OER. In previous work, we have shown that ALD enables digital control over the stoichiometry of cobalt phosphate films and that this approach leads to a deeper understanding of their activation mechanism and performance. Moreover, Mattelaer et al demonstrated the feasibility of producing active manganese oxide catalysts through ALD.…”
Section: Introductionmentioning
confidence: 99%